Identifying Achievement Goals and Their Relationship to Academic Achievement in Undergraduate Pharmacy Students - Alrakaf, Saleh (American Journal of Pharmaceutical Education, 2014)
Objectives. To compare the achievement goal orientations of first-year with those of third-year undergraduate Australian pharmacy students and to examine the relationship of goal orientations to academic achievement. Methods. The Achievement Goal Questionnaire was administered to first-year and third-year students during class time. Students’ grades were obtained from course coordinators. Results. More first-year students adopted performance-approach and mastery-approach goals than did third-year students. Performance-approach goals were positively correlated with academic achievement in the first year. Chinese Australian students scored the highest in adopting performance-approach goals. Vietnamese Australian students adopted mastery-avoidance goals more than other ethnicities. First-year students were more strongly performance approach goal-oriented than third-year students. Conclusion. Adopting performance-approach goals was positively correlated with academic achievement, while adopting avoidance goals was not. Ethnicity has an effect on the adoption of achievement goals and academic achievement.